Answer:
(x-3)^2 + (y+2)^2 = 9^2
Step-by-step explanation:
x^2 -6x+y^2+4y-68 = 0
Complete the square
x^2 -6x+y^2+4y-68+68 = 0+68
x^2 -6x+y^2+4y = 68
Find the term to add for x
-6 /2 = -3 -3^2 = 9
Find the term to add for y
4/2 =2 2^2 = 4
Add 9 and 4
x^2 -6x+9+y^2+4y+4 = 68+9+4
(x-3)^2 + (y+2)^2 = 81
(x-3)^2 + (y+2)^2 = 9^2
The standard form is
(x-h)^2 + (y-k)^2 = r^2 where (h,k) is the center and r is the radius
Answer:
5 years.
Step-by-step explanation:
Every year the population increases by a factor 103.5% or 1.035.
The equation relating population and time in years is:
P = 6000(1.035)^t (This is an example of exponential growth)
So we have:
7100 = 6000(1.035)^t
(1.035)^t = 7100/6000
(1.035)^t = 1.1833
t ln 1.035 = ln 1.1833
t = ln 1.1833/ln 1.035
= 4.89.
X = 5y + 30/4 - 3 is the answer.
Answer:
the hourly rates are $8 and $10 respectively
Step-by-step explanation:
Given that
The generator rents for 6 hours and the total cost is $48
And, for another job The generator rents for 4 hours and the total cost is $40
We need to find out the hourly rates
For the first one
= $48 ÷ 6 hours
= $8
For the second one
= $40 ÷ 4 hours
= $10
Hence, the hourly rates are $8 and $10 respectively
9/12 so 12 triés because 9*3=27 so you then have to multiply 4*3*12